Analisis Karakteristik Aliran Irigasi Perforasi Pada Lahan Datar: Analysis of Perforated Irrigation Flow Characteristics on Flat Land - I Dewa Gede Jaya Negara; Anid Supriyadi; Agus Suroso; Humairo Saidah; Heri Sulistiyono; Abdi Fadillah (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Perforation irrigation is a unidirectional beam irrigation system that can be used for crop irrigation on dry land, due to the efficient use of water and the ability to wet land with a limited area. Therefore, the perforation irrigation system needs to be studied further in relation to the area of land that can be irrigated and the distribution of discharge to each perforated pipe. By testing several variations of the water level, the perforation irrigation emission capability will be obtained in the form of irrigation distribution, uniformity, emission capability and discharge amount used in irrigation on flat land. This study aims to determine the perforation irrigation capacity on flat land, the distribution of irrigation and the amount of discharge required. The test was carried out on three perforated pipes made of ½” PVC as lateral pipes, three transmission pipe length variations, such as 0.8m, 1m, and 1.2m with a distance between the perforations of 60 cm. The source of irrigation water comes from a 3 m tall tower with a capacity of ± 200 ????????????????????. The test uses three variations of head height, namely h1 350 cm, h2 360 cm, h3 370 cm and h4 380 cm. The results showed that the perforation irrigation jet length was around 100cm -120 cm, the uniformity of CU irrigation was above 97% with a total discharge on h1 QT = 0.689 lt/s, h2 QT = 0.690 lt/s , h3 QT = 0.695 lt/s and on h4 QT = 0.701 lt/s. While the range of flow rates for perforation 1 pipe Q1 (0.42 lt/s – 0.429 lt/s), perforation 2, Q2 (0.13 -0.145 lt/s) and perforation 3, Q3 (0.129 - 0.135 lt/s)